Fully Flexible, Highly Conductive Threads Based on single walled carbon nanotube (SWCNTs) and poly (3, 4 ethylenedioxy thiophene) poly(styrenesulfonate) (PEDOT:PSS). Issue 10 (3rd September 2021) - Alhashmi Alamer, Fahad; Badawi, Nujud M.
Abstract : Herein, the morphological, electrical, thermal, and structural properties of conductive threads prepared using PEDOT:PSS, SWCNTs, and a layer combination of both are investigated. The primary finding of this work is that the layer thread has lowest resistance of 0.0072 Ω compared with 0.0211 Ω for SWCNTs alone and 0.0528 Ω for PEDOT:PSS alone. This lowest resistance is achieved with 1.729 mg of constituent compared with 1.870 mg of SWCNTs and 79.81 mg of PEDOT:PSS to obtain the respective resistances of 0.0211 and 0.0528 Ω. The layer thread therefore achieves lowest resistance with the least amount of material, in particular PEDOT:PSS. All resistances exhibit metallic behavior as a function of temperature up to 90 °C, and this behavior is stable for a period of at least 3 months. Abstract : Herein, the morphological, electrical, thermal, and structural properties of conductive threads prepared using PEDOT:PSS, SWCNTs, and a layer combination of both are studied. The layer thread is found to have the lowest resistance compared to the other samples. All resistances exhibit metallic behavior and are stable for a period of at least 3 months.